A VIRTUOUS PANDEMIC? (IM)MORAL RESPONSES TO BLACK DEATH IN DANIEL DEFOE'S A JOURNAL OF THE * PLAGUE YEAR - Arıkan, Seda (My University, 2022)
Throughout the history, humanity has suffered many pandemics which people have responded to in various ways, struggled to cope with, and ultimately survived. As the history has made humanity witness, there is not even one pandemic until now which humanity has not come through. However, to survive a pandemic requires multiple capabilities, not only physical, social, and ?nancial, but most importantly a moral capability. In this sense, the narratives of pandemic are stimulating to discern how moral and immoral attitudes are adopted while going through hard times. In the light of it, Daniel Defoe's A Journal of the Plague Year published in 1722 sheds light on the Great Plague of London in 1665 by using a rationalist point of view which places the novel among realist historical narratives. However, Defoe's documentation of the 1665 plague is also a narrative of morality that depicts and gives insight into how people behave in the times of a pandemic and respond to them morally or immorally. Considering Defoe's range of people–the wealthiest people running away from the city at once, the governors who quarantine houses leaving people to death, the ignorant infectious people spreading the plague, the fraud ecclesiastics, physicians, and magicians who exploit people; and the ones who prefer to survive by taking care of each other–A Journal signs how the people who are suffering and the others who take advantage of their suffering give moral or immoral responses to a fatal pandemic. To provide an insight into the current (im)moral responses to today's Covid-19 pandemic, this study is an effort to make the place of moral philosophy, and speci?cally virtue ethics, visible in the narrative of Defoe which could be accepted as a call from over the centuries.
Keywords: Pandemic; Plague; Virtue Ethics; Daniel Defoe; A Journal of the Plague Year